PENGARUH PENGETAHUAN WAJIB PAJAK, TINGKAT KESADARAN WAJIB PAJAK DAN TINGKAT PENDAPATAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN (PBB) DI KABUPATEN SLEMAN TAHUN 2018-2021 - Pur Dwiastuti, Maria Magdalena; Supardi, Supardi; Astuti, Yuli (PRIMA EKONOMIKA, 2024)
Taxes are a reliable source of government revenue including land and building taxes. Land and building taxes are none other than because the object of tax covers all land and building in Indonesia. Many factors influence taxpayer compliance in paying taxes, including knowledge, level of awareness, and income level of taxpayers. This study aims to analyze the effect of taxpayer knowledge, taxpayer awareness level and taxpayer income level on taxpayer compliance in paying land and building tax in Sleman Regency. The population in this study are taxpayer, land and building taxes registered in Sleman Regency in 2021 of 644,479 taxpayers. The sampling technique used purposive sampling and random sampling techniques. The data analysis used is quantitative data analysis, with multiple regression analysis methods and partial tests to prove the hypothesis using the SPSS 25 program.. The results of this study indicate that taxpayer knowledge, taxpayer awareness, and taxpayer income levels have a positive and significant partial effect on taxepayer compliance, land and building tax in Sleman Regency. In the multiple linear regression test it can be seen that the variable knowledge of the taxepayer, the level of awareness of taxepayer and the level of income of the taxpayer has a positive influence on taxepayer compliance, meaning that the higher the knowlagde of the taxpayer, the higher the level of awareness of the taxpayer and the higher the income level of the taxpayer the higher the compliance of taxpayers in paying land and building taxes in Sleman Regency. Key word : Tax, Property tax, Awareness, Compliance